163ASCENDING THORACIC AORTIC ANEURYSM WALL STRESS ANALYSIS USING PATIENT-SPECIFIC FINITE ELEMENT MODELLING OF IN VIVO MAGNETIC RESONANCE IMAGING. (October 2014) - Ge, L.; Krishnan, K.; Hope, M.; Saloner, D.; Guccione, J.; Tseng, E.E.
Abstract : Objectives: Rupture/dissection of ascending thoracic aneurysms (aTAA) carries a high mortality and occurs in many patients who had not met size criteria for elective surgical repair. Wall stress may be a better predictor than size for adverse events, but cannot be directly measured in vivo, rather determined from fluid structure interaction (FSI) simulations. Current computational models are fraught with assumptions that limit accuracy. The study purpose was to develop the first patient-specific aTAA model using in vivo magnetic resonance imaging (MRI) to assess wall thickness, material properties and stress-free 3D-geometry. Methods: aTAA patients underwent 4D-flow DENSE (displacement encoding with stimulated echo) MRI. Lumen geometry and wall thickness were used to create surface contour meshes of aTAA geometry. DENSE measured circumferential and longitudinal aortic wall strain and wall material property was derived using inverse analysis. Zero-stress geometry was derived using a novel fast pre-stress approach. Results: Peak von Mises stress of FSI model with zero-pressure correction was 465 kPa, while without zero-pressure correction the model predicted 272 kPa. Average von Mises stress predicted by zero-pressure correction FSI model was 98 ± 18 kPa, while that for non-zero-pressure correction was 86 ± 16 kPa. Conclusion: aTAA models in the literature have not accounted for zero-stress configuration or patient-specific material property. We demonstrate that in vivo MRI can be used to obtain patient-specific parameters that significantly impact wall stress results. Future computational models that use wall stress to predict aTAA adverse events must take into account zero-stress geometry and patient material property for accurate wall stress determination.